Beyond the racial state : rethinking Nazi Germany - Pendas, Devin O. 1966- HerausgeberIn; Roseman, Mark 1958- HerausgeberIn; Wetzell, Richard F. 1961- HerausgeberIn (Publications of the German Historical Institute, 2017)
"Over the past fifteen or twenty years, scholarship on the Third Reich has increasingly recognized the centrality of racial thought to the formulation of policy in a wide array of fields. During the 1980s, scholars began to depict the Third Reich as, in Michael Burleigh and Wolfgang Wippermann's resonant phrase, a 'racial state.' Moving away from an exclusive focus on anti-Semitism, this racial turn broadened the understanding of Nazi racial policy. It expanded awareness of the range of Nazi victims, incorporating, for instance, the murder of the mentally and physically handicapped, and also the sterilization and incarceration of people considered 'asocial,' into a comprehensive account of Nazi biopolitics. This approach also broached the question of how broad the support for Nazi racial policies was, interrogating the extent to which ordinary Germans cooperated in the projects of the racial state, for instance, as mothers of 'Aryan' children or as supervisors of 'racially inferior' forced laborers. While the benefits of this approach have been significant, it has become increasingly clear in the last few years that the racial state paradigm has begun to obscure as much as it reveals about the reality of the Third Reich. First, this approach tends to reify race as an epistemological category, presenting it as more coherent and comprehensive than it in fact was. The Nazis themselves were aware of the internal tensions and contradictions that plagued any effort to articulate a coherent and comprehensive racial 'science.' Second, the ongoing salience of alternative categories of identity in the Third Reich (ethnic, völkisch, religious, class-based) is difficult to explain within the racial state paradigm. Third, the racial turn blurs the tensions between, on the one hand, specifically racial ideas and policies and, on the other hand, broader traditions of domination and empire-building that acquired at most a superficial racial gloss during the Third Reich. Questions of military necessity or economic advantage coexisted with biopolitical projects"--From German Historical Institute website